THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, LEVERAGE, CAPITAL INTENSITY, AND INVENTORY INTENSITY ON TAX AVOIDANCE (CASE STUDY ON CONSUMER GOODS COMPANIES REGISTERED ON THE INDONESIA STOCK EXCHANGE) - Virani, Virani (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
This research aims to know the influence of Corporate Social Responsibility (CSR), Leverage, Capital Intensity and Inventory Intensity on Tax Avoidance. The independent variables used in this research are CSR, Leverage, Capital Intensity and Inventory Intensity. While, the dependent variable used in this research is Tax Avoidance. This research is using quantitative research method and using two year annual reports (2016-2017) of consumer goods companies registered on the Indonesia Stock Exchange (IDX). The samples that listed on the IDX in 2016-2017 are selected by using purposive sampling method with certain criteria and 23 banking sector companies are obtained.REFERENCES Anindyka, D., Pratomo, D., &Kurnia. (2018). Pengaruh Leverage (DAR), Capital Intensity dan Inventory Intensity Terhadap Tax Avoidance, Universitas Telkom, Indonesia.Consultant, D. (2011). Uji Normalitas. Retrieved from http://duwiconsultant.blogspot.com/2011/11/uji-normalitas.htmlDeegan, C., Rankin, M., & Tobin, J. (2002). An Examination of the Corporate Social and Environmental Disclosures of BHP from 1983-1997: A Test of Legitimacy Theory. Accounting, Auditing and Accountability Journal 15(3), 312-343.DeFond, M., & Hung, M. (2001). An Empirical Analysis of Analysts? Cash Flow Forecast. USC Leventhal School of Accounting Working Paper.Dowling, J., & Pfeffer, J. (1975). Organizational Legitimacy: Social Values and Organizational Behavior. California: University of California Press.Dwilopa, D. E. (2015). Pengaruh Corporate Social Responsibility, Capital Intensity, dan Perencanaan Pajak Terhadap Penghindaran Pajak, Universitas Muhammadiyah Yogyakarta, Indonesia.Freeman, R. (1984). Strategic Management: A Stakeholder Approach. Boston: Pitman.Ghozali, I. (2013). Aplikasi Analisis Multivariate dengan Program SPSS Cetakan VII. . Semarang: Badan Penerbit Universitas Diponegoro.Gorethai, J. (2019). The Impact of Intellectual Capital Performance on Intellectual Capital Disclosure in Financial Report (Case Study on Banking Sector Companies Registered on the Indonesia Stock Exchange), Universitas Tanjungpura, Indonesia.Hery. (2015). Analisis Laporan Keuangan Pendekatan Rasio Keuangan. Yogyakarta: Center of Academic Publishing Service.Hidayat, T. (2017). Pengaruh Pengungkapan Corporate Social Responsibility dan Struktur Kepemilikan Terhadap Praktik Penghindaran Pajak, Universitas Muhammadiyah Surakarta, Indonesia.Johnston, M. (2013). Secondary Data Analysis: A Method of which the Time Has Come. Qualitative and Quantitative Methods in Libraries (QQML) 3, 619 ?626.Kotler, P., &Lee, N. (2005). Corporate Social Responsibility : Doing the Most Good for Your Company and Your Cause. New York: John Wiley & Sons Inc.Lauvira, T., Syafitri, Y., & Parlindungan, R. (2018). Pengaruh Persepsi Wajib Pajak Mengenai ProgramPerpajakan Tax Amnesty dan Wacana Transparasi Data Nasabah Bank (Bank Secrecy) Tahun 2018 Terhadap Kepatuhan WajibPajak (Studi Empiris pada KPP Pratama Ilir Barat Palembang), STIE Multi Data Palembang, Indonesia.Mardiasmo. (2009). Perpajakan; Edisi Revisi 2009. Yogyakarta: Penerbit Andi.Muzakki, M. R., &Darsono (2015). Pengaruh Corporate Social Responsibility dan Capital Intensity Terhadap Penghindaran Pajak. Diponegoro Journal of Accounting, 1-8Naraduhita , D., & Sawarjuwono, T. (2012). Corporate Social Responsibility: Upaya Memahami Alasan Dibalik Pengungkapan CSR Bidang Pendidikan. Jurnal Akuntansi & Auditing, 96.Palan, R., Murphy, R., & Chavagneux, C. (2008). Tax Havens: How Globalization Really Works. Canada: Cornell University Press.Park, S. J. (2017). Corporate Social Responsibility and Tax Avoidance: Evidence From Korean Firms, Anyang University, South Korea.Pradipta, D. H., & Supriyadi (2014). Pengaruh Corporate Social Responsibility (CSR), Profitabilitas, Leverage, dan Komisaris Independen Terhadap Praktik Penghindaran Pajak, Universitas Gadjah Mada, Indonesia.Priyatno, D. (2010). Teknik Mudah dan Cepat Melakukan Analisis Data Penelitian Dengan SPSS. Yogyakarta: Gava Media.PT Bursa Efek Indonesia. (2018). Laporan Keuangan dan Tahunan. Retrieved from Bursa Efek Indonesia: http://www.idx.co.id/.Purniyasari, S. (2014). Pengaruh Pengungkapan CSR Terhadap Penghindaran Pajak, Universitas Negeri Surabaya, Indonesia.Putri, C. L. &Lautania, M. F. (2016). Pengaruh Capital Intensity Ratio, Inventory Intensity Ratio, Ownership Structure dan Profitability Terhadap Effective Tax Rate (ETR) (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011 -2014), Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi (JIMEKA), 101-119.Putri, S. D. A. (2015). Analisis Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Tax Avoidance (Penghindaran Pajak), Jurnal Akuntansi Indonesia, Indonesia.Rahardjo, Budi. 2007. Keuangan Dan Akuntansi. Yogyakarta: Graha Ilmu.Rahma, U. T. (2016). Pengaruh Ukuran Perusahaan dan Corporate Governance Terhadap Tax Avoidance(Survei Pada Perusahaan Manufaktur Sub Sektor Outomotif Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2015), Universitas Komputer Indonesia, Indonesia. Sandra, M. Y. D., &Anwar, A. S. H. (2018). Pengaruh Corporate Responsibility dan Capital Intensity Terhadap Penghindaran Pajak, Universitas Muhammadiyah Malang, Indonesia.Sari, L. L. P., &Adiwibowo, A. S. (2017). Pengaruh Corporate Social Responsibility Terhadap Penghindaran Pajak Perusahaan, Universitas Diponegoro, Indonesia.Sugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Bandung: AlfabetaSuyanto, Dwi, K., & Suparmono. (2012). Likuiditas, Leverage, Komisaris Independen, dan Manajemen Laba Terhadap Afresivitas Pajak Perusahaan. Jurnal Keuangan dan Perbankan 16(2), 167-177.Undang Undang No. 28 Tahun 2007 Pasal 1 Ayat 1. (n.d.).Undang Undang Perseroan Terbatas Nomor 40 Tahun 2007. (n.d.).Utomo, J. G. (2017). Pengaruh Corporate Social Responsibility Profitabilitas, Leverage, Komisiaris Independen dan Ukuran Perusahaan Terhadap Penghindaran Pajak, Universitas Dian Nuswantoro Semarang, Indonesia.Wibisono, Y. (2007). Membedah Konsep dan Aplikasi CSR (Corporate Social Responsibility). Gresik: Fascho Publishing.Wiguna, P. P., &Jati, K.(2017). Pengaruh Corporate Social Responsibility, Preferensi Risiko Eksekutif, dan Capital Intensity Pada Penghindaran Pajak, Universitas Udayana, Indonesia.Wijayanti, A., Wijayanti, A., & Chomsatu, Y. (2017). Pengaruh Karakteristik Perusahaan, GCG dan CSR Terhadap Penghindaran Pajak. Journal of Economic and Economic Education 5(2), 113-127.